Vol. 13 No. 1 (2024): VIA PANORAMICA | Summer Issue 2024 | The Dispossessed: 50 years since 50 years hence - Caetano, Joana (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
It is a happy coincidence that VIA PANORAMICA has come to a turning point in the same year that we celebrate the 50th anniversary of Ursula K. Le Guin’s publication of The Dispossessed: An Ambiguous Utopia. There are many reasons why I selected this literary event as the theme of my first VIA PANORAMICA, but namely the fact that this novel is in itself a turning point in the utopian tradition and epitomises a new way of thinking and writing Science Fiction. Besides investing in a thematic section and a new design, there are also new subsections to stimulate contributions by undergraduate students, illustrators and other artists, as a conscious attempt to involve the younger generation of academics as well as senior researchers, and also open up Anglo-American Studies to the Arts by inviting colleagues from other areas to think about and express their love of literature. Therefore, it is with great pleasure that the Editors introduce VIA PANORAMICA Vol. 13 N.º 1: The Dispossessed: 50 years since 50 years hence | A Journey Towards Utopian Science Fiction. We invite you to see this issue first by accessing the link to have a preview of our new design and then select the articles you are most interested in for a more attentive reading.